2013
DOI: 10.1016/j.jtcvs.2012.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarkers for distinguishing etiologic subtypes of thoracic aortic aneurysm disease

Abstract: Background Thoracic aortic aneurysms (TAAs) develop through an asymptomatic process resulting in gross dilatation that progresses to rupture if left undetected and untreated. If detected, TAA patients are followed over time until the risk of rupture outweighs the risk of surgical repair. Current methodologies for tracking TAA size are limited to expensive computed tomography or magnetic resonance imaging, as no acceptable population screening tools are currently available. Previous studies from this laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 20 publications
2
112
0
Order By: Relevance
“…MMPs, particularly MMP2, are best known as ECM-degrading enzymes, and as such, they are often associated with adverse outcomes in vascular pathologies. 20,21,41 In this study, we demonstrate 2 opposing roles for MMP2 in aortic wall remodeling whereby it contributes to production in addition to degradation of the ECM structural proteins. Ang II is a peptide hormone upregulated in several cardiovascular diseases and can trigger a range of cellular responses, including synthesis of ECM proteins, as well as enhanced proteolytic activities through activation of MMPs, such as MMP2.…”
Section: Discussionmentioning
confidence: 64%
“…MMPs, particularly MMP2, are best known as ECM-degrading enzymes, and as such, they are often associated with adverse outcomes in vascular pathologies. 20,21,41 In this study, we demonstrate 2 opposing roles for MMP2 in aortic wall remodeling whereby it contributes to production in addition to degradation of the ECM structural proteins. Ang II is a peptide hormone upregulated in several cardiovascular diseases and can trigger a range of cellular responses, including synthesis of ECM proteins, as well as enhanced proteolytic activities through activation of MMPs, such as MMP2.…”
Section: Discussionmentioning
confidence: 64%
“…Tzemos et al [11] reported significant elevation of plasma MMP-2 in non-stenotic BAV patients with ascending aorta dilatation, while their plasma MMP-9 levels hardly altered. On the contrary, Ikonomidis et al [28] advocated the predictive value of plasma MMP-9 for identifying ascending aortic aneurysm among BAV patients, regardless of their aortic valve status. We hypothesized that there might be different aortic vessel wall shear stress thresholds for the activation of these two enzymatic proteins, since MMP-2 was synthesized by resident cells within aortic wall such as fibroblasts and smooth muscle cells and expressed ubiquitously under physiological conditions, while MMP-9 existed mainly not only in neutrophils but also in other cell types responding to specific stimuli [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Neither did we find significant relations with aortic dimensions as measured by echocardiography, although a trend was observed for MMP-2 (adjusted p value 0.087). Previous studies have reported altered plasma MMP-2, -9 and TIMP-1 levels in patients with aortic valve stenosis and ascending aorta dilatation, both in bicuspid valves and in chronic thoracic aortic dissection (Ikonomidis et al, 2013;Wang et al, 2016;Zhang et al, 2014). It may therefore be worthwhile to evaluate MMPs in specific patient subgroups with a high risk of aortic dilatation, in combination with more detailed imaging modalities of the aorta, such as CT or MRI.…”
Section: Aortic Stenosis and Dilatationmentioning
confidence: 99%
“…More specific, altered MMP-2, MMP-9 and TIMP-1 levels have been associated with left ventricular (LV) hypertrophy, chronic heart failure and diastolic dysfunction in hypertensive heart disease and coronary artery disease (Ahmed et al, 2006;Chu et al, 2013;Kang et al, 2008;Laviades et al, 1998;Martos et al, 2007). In patients with thoracic aortic aneurysms, specific MMP-2, -9 and TIMP-1 profiles have been described; however, the majority of research in this field is based on histology of the aortic wall rather than circulating blood biomarker levels (Ikonomidis et al, 2013;Wang et al, 2016;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%